Open-labeled randomized controlled trial to evaluate the 1-year clinical outcomes of polymer-free sirolimus-eluting coronary stents as compared with biodegradable polymer-based sirolimus-eluting coronary stents - Viswanathan, Sunitha (Indian Heart J, 2018)
BACKGROUND: Head to head trials of clinical outcomes of sirolimus eluting polymer free vs. biodegradable polymer stents are lacking. METHODS: Single centre prospective open labeled randomised controlled clinical trial. Basis for sample size calculation was the rate of MACE from the ISAR TEST 3 trial in which the absolute difference was 10.25% with a standard deviation of 0.24. Assuming null hypothesis, 80% power and 5% alpha error, to detect a 10% difference, adjusting for 10% loss of follow up, sample size was 204. Inclusion criteria: Patients with stable coronary artery disease or recent acute coronary syndrome ( >1 week from the date of STEMI), being taken up for elective angioplasty. End points: Primary end point was MACE at 1 year and secondary end points at the end of 1 year were cardiac death, urgent target lesion revascularization, acute coronary syndrome, stroke and in-stent re-stenosis. RESULTS: 204 patients were enrolled between January 2013 to July 2014, 91 in the polymer-free group and 113 in the biodegradable polymer group. Baseline characteristics were comparable between both groups. 21 patients (10.29%), were lost to follow up. MACE at 1 year were comparable in both the groups 3 of 85(3.52%) in the polymer-free group and 3 of 98(3.06%) in the biodegradable polymer group, p = 0.859. The secondary end points were also comparable between the two groups- Death- 1 of 85(1.17%) vs. 2 of 98(2.04%), p = 0.646, Stroke 0 of 85 vs. 2 of 98(2.04%), p = 0.185 and acute coronary syndrome – 2 of 85(2.35%) vs. 1 of 98(1.02%), p = 0.204. There were no instances of urgent target lesion re-vascularisation or definite stent thrombosis in either groups. In stent re-stenosis was found in 7 of 85(8.2%) in the polymer-free group vs. 6 of 98(6.12%) in the biodegradable polymer group. CONCLUSION: The 1 year MACE rates are comparable in patients who underwent elective coronary revascularization using sirolimus eluting polymer-free and biodegradable polymer stents.